Registration of Marriage Book Perspective of Needs Level Theory Abraham Maslow and Syatibi - Harwis, Harwis; Ahmad, Ahmad (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
The research aims to reveal the level of human need in the current era for the registration of marriage books. This research uses a document analysis approach and a literature study. Analysis of the Compilation of Islamic Law (KHI), the Marriage Law, and other related documents. This research explores the phenomenon of unregistered marriages in Indonesia, and the legal consequences caused by unregistered marriages and then analyzes the need level of the Indonesian people for the importance of registering marriage books using Abraham Maslow's and Syatibi's need level theory. This study concludes that the registration of marriage books in the analysis of Maslow's theory of needs level can include five levels of needs. Maslow's version of the five levels of needs is relevant to Syatibi's theory of needs at the level of primary needs (daruriyat). Unregistered marriages will result in a loss of civil rights, which can be life-threatening, especially for children born from unregistered marriages. Therefore, the current and future contexts have become a necessity for the obligation to fulfill the marriage book. Unregistered marriages will cause successive losses and crimes. Therefore, marriages without registration in a marriage book must be expressly annulled by the government with strict laws accompanied by sanctions. This research is expected to be a stimulant for scholars, legislators, and the government to have the confidence and courage to prevent unregistered marriages by the state.